Harper Hall of Pern - McCaffrey, Anne; 1956- (Garden City, NY Nelson Doubleday, Inc, 1979)
With the help of Master-harper, Menolly and her fire lizards overcome the prejudice against a woman's becoming a harper on the planet Pern
v 1. A to Anckerman.
Includes bibliographical references and index.
89671
Keywords: Dragons; Fantasy